Factors associated with the uptake of Covid-19 vaccines: A cross-sectional study among the students of Bishop Stuart University in South-western Uganda. - Mary Jesenta Ngabirano; Francis Kazibwe; Ronald Bahati; Bright Laban Waswa; Wycliffe Tumwesigye (Student's Journal of Health Research Africa, 2022)
Background: